Tracking of Vascular Measures From Infancy to Early Childhood: A Cohort Study - Toby Mansell; Joel Nuotio; Peter Vuillermin; Anne‐Louise Ponsonby; Deborah A. Lawlor; Kate McCloskey; Markus Juonala; David P. Burgner (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atherosclerosis develops across the life course, and variation in aortic intima‐media thickness (IMT) is evident from infancy onward, although most early‐life data are cross‐sectional. We investigated whether abdominal aortic IMT at age 6 weeks is associated with vascular measures at 4 years and the relationship of prenatal and perinatal exposures with these measures in early childhood. Methods and Results We analyzed data from 518 participants with 6‐week and 4‐year vascular measures from the Barwon Infant Study. Aortic IMT was measured at 6 weeks (mean, 6.1±SD 1.5 weeks) and aortic and carotid IMT, carotid–femoral pulse wave velocity, and blood pressure at 4 years of age (4.3±0.3 years). Associations of early‐life exposures—maternal enteric microbiome, smoking and low‐density lipoprotein cholesterol during pregnancy, birth weight, and gestational age—were also investigated. In the primary model, 6‐week aortic IMT (649±66 μm) was associated with small differences in 4‐year carotid IMT (453±45 μm) (mean difference in carotid IMT per 100 μm higher 6‐week aortic IMT=7.0 μm [95% CI, 0.7–13.3]; P=0.03), with no evidence for associations with 4‐year aortic IMT, pulse wave velocity, or blood pressure. Higher birth weight was associated with greater 4‐year aortic IMT, and maternal smoking with higher systolic blood pressure. Conclusions Vascular measures do not show strong evidence of tracking between infancy and early childhood. Longitudinal studies with repeated assessment beyond age 4 years would inform optimal timing of early prevention and targets for primordial prevention.